Amicitia in sociability networks in the Roman Republic: the case of Cicero and Pompey (Ágora Journal, 2024)
Within the scenario of disputes to political consolidation and crises in the last century of the Roman Republic, the networks of interpersonal interaction emerge as a primable resource for those public individuals who sought to ascend in the public career. Thus, seeking to broaden the discussion about the magnificence of sociability within the Roman Republic, the article turns to the figure of Senator Marco Túlio Cicero, who as a new man greatly enjoyed his interdependent relationships. Discussing the malleability of these bonds at the time, the relevance of the Ciceronian amicitia as a tool for crisis resolution is considered. In this discussion, the approach between Cicero and Pompey is exposed, reflecting on how this sociability between the parties ensured a reciprocal influence on the construction of their careers.
Keywords: Cícero; sociability; amicitia